(untitled) (Journal of Student Affairs in Africa, 2021)
As reflective practitioners working in disability inclusion, we constantly work with shifting realities concerning our students, who are not a homogenous group. The coronavirus pandemic (Covid‑19) was a reality least expected in 2020, yet we used our flexible approach to make the transition as smooth as we possibly could. The Disability Unit (DU) is one of five units located within the Centre for Student Counselling and Development at Stellenbosch University (SU) and falls within the responsibility centre of the Deputy Vice-Chancellor: Teaching and Learning. The DU was founded in 2007 and is 15 years old in 2021. We aim to foster disability inclusion within a transformative framework at SU, with our main focus on students with disabilities. Our wider aim is universal access, which includes working towards the removal of cultural, social, language and disability barriers in the higher education context. We are guided by the Disability Access Policy (2018) of SU. Since the latter part of March 2020, we had to shift to online teaching and learning. This came at a time when we were preparing for the end of the term and student support was being put in place. The onset of Covid‑19 occasioned unanticipated reflections and challenges, which we share in this article. We also reflect on what we have learnt and how we can move forward in a changed academic environment catapulted into a digital world. We do this reflection by following the Gibbs’ reflective cycle (Gibbs, 1988) which offers a way to reflect and learn from experience. The cycle is weaved into the reflections as it follows a process of describing the context of the DU, expressing how the Covid‑19 pandemic was felt by staff and students, evaluating and learning from what was experienced. According to Lyner-Cleophas (2020), online learning has benefits and challenges, especially considering students with disabilities.